2002
DOI: 10.1136/jnnp.73.6.733
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative mapping of the cortical areas involved in multiplication and subtraction: an electrostimulation study in a patient with a left parietal glioma

Abstract: Objectives: Advances in neuroimaging studies have recently improved the understanding of the functional anatomy of the calculation processes, having in particular underlined the central role of the angular gyrus (AG). In this study, the authors applied this knowledge to the surgical resection of a glioma invading the left AG, by localising and sparing the cortical areas involved in two different components of calculation (multiplication and subtraction), using direct electrical stimulations. Methods: A calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…6 Calculation processing may be monitored during surgery in different areas, such as left frontal, temporal, and parietal cortices. 5,11,13 As far as the right hemisphere is concerned, we recently confirmed previous neuroimaging 1,2,10,12 and transcranial magnetic stimulation 14 data, suggesting a role of the right cortex in calculation processing. 4 Conversely, no surgical data have been reported in the literature on subcortical mapping of right parietal white matter so far.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…6 Calculation processing may be monitored during surgery in different areas, such as left frontal, temporal, and parietal cortices. 5,11,13 As far as the right hemisphere is concerned, we recently confirmed previous neuroimaging 1,2,10,12 and transcranial magnetic stimulation 14 data, suggesting a role of the right cortex in calculation processing. 4 Conversely, no surgical data have been reported in the literature on subcortical mapping of right parietal white matter so far.…”
Section: Discussionsupporting
confidence: 75%
“…Intraoperatively, cortical and subcortical mapping was performed using a bipolar stimulator. A functional cortical map was obtained using the method described by Duffau et al 5 Calculation tasks were administered as previously reported. 4 A bipolar probe with 5-mm-spaced tips delivering a biphasic current was applied to the cortex for a period of 4 seconds (with a pulse frequency of 60 Hz and a single pulse phase duration of 0.3 msec).…”
mentioning
confidence: 99%
“…9,21) A left parieto-occipital glioma invading the angular gyrus was successfully removed using calculation task monitoring without deterioration of the calculation ability. 9) Gerstmann's syndrome was demonstrated by direct stimulation of the left angular gyrus and is often associated with various types of aphasia, depending on the stimulation sites or lesions of the cortical areas in the left parietal lobe. 21) The six Awake Surgery to Preserve Calculation Ability monitoring tasks included standard naming, reading, calculation, finger recognition, color naming, and writing.…”
Section: Discussionmentioning
confidence: 99%
“…19) So far, very few attempts have been made to map the calculation center during surgery. 9,21) We describe a case of surgical resection of glioblastoma located near the left angular gyrus, using awake surgery with functional mapping of language and calculation functions.…”
Section: Introductionmentioning
confidence: 99%
“…of human cortex, despite the anatomical boundaries are organizationally related and surgical resection can basically considered a breach of Preoperative and intraoperative brain mapping, separating the normal from the abnormal function and allows resection of lesions that previously could not even imagine (8). Current studies recommend standard use of intraoperative electrical stimulation of the brain during operations in eloquent brain zone, a method that improves postoperative functional outcome (5,4,16,31).…”
Section: Bogosavljevic V Et Al: Technique Of Cortical Electrostimulamentioning
confidence: 99%